HUBUNGAN LAMA PAPARAN ASAP PEMBAKARAN ARANG TERHADAP JUMLAH RETIKULOSIT DARAH PADA PEDAGANG SATE DI WONOCOLO SURABAYA - Safitri, Firda Eka; Nugraha, Gilang; Santoso, Andreas Putro Ragil; Nidianti, Ersalina (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2023)
Charcoal burning techniques contain harmful pollutants in the form of particulates, carbon monoxide (CO), polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), heavy metals and other toxic compounds which have short and long term impacts on the environment and human health. One of the chemical substances contained from the burning of satay traders' charcoal is carbon monoxide. Carbon monoxide (CO) when inhaled into the lungs will join the blood circulation and will block the entry of oxygen needed by the body. This can happen because CO gas is toxic, it also reacts metabolically with blood (hemoglobin). So that the erythrocyte cells lack oxygen which causes damaged erythrocytes and an increase in reticulocytes and erythrocytes. The purpose of this study was to prove that there is a relationship between prolonged exposure to charcoal burning smoke and the number of reticulocyte cells in satay traders. This study used an analytic observational method with a cross sectional approach. This study used 20 samples of venous blood from Madura satay traders who live in one place in the Wonocolo sub-district, Surabaya. Test analysis using Spearman correlation test. Based on the results of the study, the average reticulocyte level was 1.2% and the average length of exposure (hours/month) was 5,35 (hours/week). Spearman correlation test results (alpha) = 0.006 <0.05 with a correlation coefficient of 0.592 means that there is an increase in the length of exposure variable with the number of reticulocytes and suggestions for further research is to examine blood reticulocytes with other methods.